Development of Secretory Lactococcus Lactis Vectors with Characterized Heterologous Signal Peptide from Pediococcus Pentosaceus - Baradaran, Ali (2010)
Lactococcus lactis, the model of lactic acid bacteria (LAB), is a generally regarded as safe (GRAS) organism and one of the most widely used LAB in the food industry. The potential application of Lactococcus lactis as a live vehicle for the production and delivery of heterologous protein for industrial and medical applications are on the rise. Investigation of heterologous protein production in different location of L. lactis revealed that secretion is preferable to cytoplasmic production. Although considerable attentions have been given to the development of efficient gene expression and protein secretion systems, however, there is still an acute lack of system to secrete heterologous proteins in L. lactis. The Gram-positive low GC content bacterium, Pediococcus pentosaceus was isolated from a local herbal plant Polygonum minus and identified by biochemical and 16S rRNA sequencing. The nucleotide sequence of the cell wall binding protein from P. pentosaceus was amplified by polymerase chain reaction (PCR), cloned into Zero Blunt® TOPO® plasmid and transformed into Escherichia coli. The coding region of signal peptides (SP) SPK1 and SPK3 were amplified from the cell wall binding proteins of P. pentosaceus and studied by in silico analysis. The in silico analysis of signal peptide revealed that SPK1 has higher hydrophobicity, GRAVY index, aliphatic index and more stability compared to SPK3 and USP45. The gene coding region of green fluorescent protein (GFP) and L. lactis signal peptide USP45 were then amplified by using Pfu DNA polymerase. Secretion cassettes were constructed using GFP as the reporter protein and USP45 as the control. Then, the SP-GFP cassette was cloned into L. lactis expression vectors pNZ8084 and pMG36e (inducible and constitutive) resulting in pNZK801, pNZK803, pNZU801 and pMGK36e1, pMGK36e3, pMGU36e1, respectively. The constructed plasmids were electro-transformed into L. lactis strain MG1363 and NZ9000 as host. Recombinant plasmids were identified by restriction enzyme digestion and sequence analyses. Western blot and ELISA analysis of transformants indicated the potential of the signal peptides SPK1 and SPK3 from P. pentosaceus to be used as a secretory signal for heterologous protein secretion in L. lactis.